Control interno del área financiera basado en el modelo coso a la compañía Nusyen S.A. 2021 - Torres Cabezas, Melanny Nicole (2021)
The present case study was carried out in the company Nusyen SA, belonging to the canton La Libertad, which is dedicated to the construction of civil works, which benefit the quality of life in the population, in addition to facilitating the circulation of vehicles and contributing to the development of the country. The main objective was to evaluate the financial area based on the COSO model, which is divided into 5 components: "control environment, risk assessment, control activities, information and communication, and finally monitoring and supervision." The application of this model allowed the identification of existing shortcomings within the area, according to the activities and operations analyzed, to then generate a detailed report of the evaluation that allows to prevent, improve organizational performance and reduce risks to the company. The applied methodology was accompanied by deductive and inductive methods with a type of exploratory and descriptive research, to analyze in depth the policies, internal regulations, functions or activities of each employee and if these are carried out efficiently within the specified deadlines. For this reason, the following techniques were implemented: the interview, directed at the manager and the general accountant; and the internal control surveys that were based on the 17 principles of the COSO model to all personnel in the financial area. This resulted in the company's employees having to improve the productivity of their operations, since a moderate level of confidence was detected and a control risk under which it should be detected and corrected in a timely manner by the internal control systems.